High‐Efficiency Polymer:Nonfullerene Solar Cells with Quaterthiophene‐Containing Polyimide Interlayers. Issue 8 (10th June 2018) - Park, Euyoung; Seo, Jooyeok; Han, Hyemi; Kim, Hwajeong; Kim, Youngkyoo
Abstract: Interfacial layers (interlayers) are one of the emerging approaches in organic solar cells with bulk heterojunction (BHJ) layers because the solar cell efficiency can be additionally improved by their presence. However, less attention is paid to the use of interlayers for polymer:nonfullerene solar cells, which have strong advantages over polymer:fullerene solar cells. In addition, most polymers used for the interlayers possess a low glass transition temperature ( T g ). Here, it is demonstrated that two types of quarterthiophene‐containing polyimides (PIs) with high T g (>198 °C), which are synthesized using pyromellitic dianhydride (PMDA) and cyclobutane‐1, 2, 3, 4‐tetracarboxylic dianhydride (CTCDA), can act as an interfacial layer in the polymer:nonfullerene solar cells with the BHJ layers of poly[(2, 6‐(4, 8‐bis(5‐(2‐ethylhexyl)thiophen‐2‐yl)‐benzo[1, 2‐ b :4, 5‐ b ′]dithiophene))‐ alt ‐(5, 5‐(1′, 3′‐di‐2‐thienyl‐5′, 7′‐bis(2‐ethylhexyl)benzo[1′, 2′‐c:4′, 5′‐c′]dithiophene‐4, 8‐dione))] (PBDB‐T) and 3, 9‐bis(2‐methylene(3‐(1, 1‐dicyanomethylene)‐indanone))‐5, 5, 11, 11‐tetrakis(4‐hexylphenyl)‐dithieno[2, 3‐d:2′, 3′‐d′]‐ s ‐indaceno[1, 2‐b:5, 6‐b′]dithiophene) (ITIC), or (3‐(1, 1‐dicyanomethylene)‐1‐methyl‐indanone)‐5, 5, 11, 11‐tetrakis(4‐hexylphenyl)‐dithieno[2, 3‐d:2′, 3′‐d′]‐ s ‐indaceno[1, 2‐b:5, 6‐b′]‐dithiophene) (IT‐M). Interestingly, the efficiency and stability of devices are improved by the PMDA‐based PI interlayers with a stretched chain structure but degraded by the CTCDA‐based PI interlayers with a bended chain structure. Abstract : Polymer:nonfullerene solar cells, of which interfacial layers consist of a quarterthiophene‐based polyimide with a linear‐shape chain structure and high thermal stability, deliver enhanced efficiency (12.2%) with improved device stability under continuous solar light illumination.